Magnitude of tuberculosis on the Bioceanic Route: an epidemiological description - Arantes da Cunha, João Pedro (2021)
This study aims to assess the epidemiological situation of five municipalities that are part of the bioceanic route in order to analyze the descriptors and general health aspect of the population through a retrospective, quantitative and cross-sectional descriptive study with a documentary approach, from secondary data reported to the National System of Notifiable Diseases in the municipalities of Guia Lopes da Laguna, Jardim, Nioaque, Porto Murtinho, Sidrolândia and Campo Grande, in the state of Mato Grosso do Sul, in the period from January 2015 to December 2020. The incidence rate ranged between 32.23 and 79.4 cases/100,000 inhabitants. There was a predominance of individuals aged between 30-39 years (26.05%) and males (67.5%). The most important injuries were alcoholism (19.15%) and smoking (18%). In the exams, 52.3% had positive bacilloscopy and 32.03% had a positive culture. The incidence of tuberculosis in the evaluated municipalities was higher than the Brazilian average and that of the state of Mato Grosso do Sul. These evaluated municipalities do not have a favorable epidemiological situation with regard to tuberculosis and the construction of the biocenic route may further aggravate the situation.